Customer satisfaction and service quality in high-contact service firm - Sarreal, Emilina R. (Animo Repository, 2008)
By taking attribute-based measures of service quality, this study establishes clear linkages between customer satisfaction (students) and quality (perception of their experience in the practicum program of the university). The results of this study clearly indicate that student satisfaction is more directly related to functional quality or process of service delivery. The delivery of service through implementation of clear policies and procedures contributed significantly to student satisfaction. The study recommends appropriate internal measures of efficiency and employee compensation as a means to ensure quality and customer satisfaction, and, as a whole, recommends a service marketing system for a high-contact type of service firm such as universities.